2021
DOI: 10.3390/children8100915
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and the Development of Moral Emotions in Children and Adolescents: A Systematic Review

Abstract: In recent years, the development of social and moral emotions (often associated to pro-social behaviors) has become the subject of increased research interest. However, the relation between these emotions and attachment is less studied. The present systematic literature review (PROSPERO: CRD42021247210) was designed to synthesize current empirical contributions that explore the link between attachment and the development of moral emotions (e.g., empathy, sympathy, altruism, and guilt) during childhood and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In addition to parental teaching styles, other variables have been studied in order to define how parents may impact their offspring’s moral development; in this regard, we found a systematic review [ 55 ], the aim of which was to identify any relation between attachment styles and the development of moral emotions: specifically, the results showed that a secure attachment at 14 years of age related to increased empathic support during observed interactions with friends across ages 16 to 18, while less secure teens developed these skills slower [ 56 ]. Furthermore, empathic sensitivity was highest in those youths with low attachment anxiety, while high attachment anxiety related to lower levels of empathic sensitivity [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to parental teaching styles, other variables have been studied in order to define how parents may impact their offspring’s moral development; in this regard, we found a systematic review [ 55 ], the aim of which was to identify any relation between attachment styles and the development of moral emotions: specifically, the results showed that a secure attachment at 14 years of age related to increased empathic support during observed interactions with friends across ages 16 to 18, while less secure teens developed these skills slower [ 56 ]. Furthermore, empathic sensitivity was highest in those youths with low attachment anxiety, while high attachment anxiety related to lower levels of empathic sensitivity [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Secure attachment as a trait emerged as a strong and consistent risk factor for compassion in the studies we reviewed. Although established in childhood and modified by life experience, secure attachment has life-long effects, influencing empathic concern in preschool-age children ( Murphy and Laible, 2013 ), the development of moral emotions ( Costa Martins et al, 2021 ), the ability to provide empathic support to peers during the teenage years ( Stern and Cassidy, 2018 ), and the quality of adult relationships ( McGinley and Evans, 2020 ). Research by Mikulincer et al (2005) and Cassidy et al (2018) demonstrated how attachment can be primed experimentally by imagining the presence of a secure, nurturing other.…”
Section: Discussionmentioning
confidence: 99%
“…The five Buddhist precepts (refrainment from killing, stealing, sexual misconduct, lying, and intoxication) are moral guidelines aimed at preventing behaviors that are considered harmful to oneself and others. Research on moral behavior indicates that morality is based in a person’s moral emotions, which are shaped by their upbringing and predispose them to prosocial behaviors [ 28 ]. In the case of insecure attachment, a person’s childhood experiences and lack of caregiver support may influence their moral compass.…”
Section: Introductionmentioning
confidence: 99%